Dito e feito: a educação pela pedra no romance de José Saramago - Souza, Kátia Pellicci Cembrone de (2024)
José Saramago was one of the most active contemporary Portuguese fiction writers. His eighteen novels reveal him as an author committed to his time, who thinks about and problematizes the human and his social relationships, while reflecting on literary work. Stone seems to be a conceptual image in Saramago’s writings: a concrete word-gesture, hard enough to provide for the crossing, just like João Cabral de Melo Neto’s word-stone, which teaches lesson by lesson throughout his poems. The proposed research seeks to confirm the hypothesis that, in the prosaic-poetic texture intertwining of the Portuguese novelist, there is a project of literary education, in which the author, by offering a fictional story aesthetically designed for the reader’s delight, also offers him literary reading and writing lessons, preparing him to read (and, perhaps, write), while he reads to be prepared. Thus, our investigation seek to 1) find out, gather and organize lessons that constitute an education for the literary inscribed by Saramago in his own artistic work 2) analyze them to understand how they are offered to the reader and 3) reveal the teacher found within the novelist/ essayist and critic interface. To this end, we base our analyzes on the concept of heterodiscourse, developed by Mikhail Bakhtin. To carry out the thesis, we read and analyze four selected novels: Manual of painting and calligraphy (1977), The stone raft (1986), The cave (2000) and Halberds, halberds, shotguns, shotguns (2014). This choice goes through Saramago’s novels, by studying four of his narratives in depth, selecting and organizing passages that highlight the object of our research and, eventually, stablishing a dialogue with others. Our research is part of comparative studies, since it articulates Literature and Literary Education, in a dialogical work between the artistic composition of Saramago’s metafictional plot and the literary theory and criticism propositions, in a two-way flow: an intense and continuous coming and going from the literary text to the theory, from the theory to the literary text, developing a critical reading by this movement